Effectiveness Digital Diorama Media To Improve Students' Concept Understanding Of Food Chain Material In Elementary School - Nurhalimah, Umi; Edi Waluyo; Decky Avrilianda; Ellianawati (Elementary Teacher Education Program, Majalengka University, 2025)
This research is motivated by the findings of students' difficulties in understanding the concept of food chains in the IPAS subject. The fact that the current generation is a digital generation accustomed to technology also supports the importance of innovation in learning. Learning resources that might aid students in comprehending abstract ideas are necessary because many educators continue to employ traditional teaching techniques. This research attempts to examine how well digital diorama media works as an educational innovation that can improve students' comprehension of the food chain concept. This study utilized a quasi-experimental approach using a non-equivalent control group design. In this study, sixty fifth-graders from Karawang Regency's SD Puri Artha participated. Students were split up into two groups: the experimental group used digital diorama material, and the control group used traditional means. Data were obtained through concept understanding tests before and after the intervention, as well as observations and interviews. According to the study's findings, pupils who used digital dioramas to learn had a significantly higher conceptual grasp than those who used traditional methods (p<0.05). Students can more easily comprehend the relationships between organisms in the food chain with the help of digital diorama media, which can offer crisper visuals. Additionally, pupils actively participate in the learning process and exhibit interest in it. The conclusion of this study is that digital diorama media is not only effective in enhancing students' understanding of the food chain concept but also in increasing students' learning motivation.